GLIKOBIOLOGI, GLIKANS DAN GLIKOPROTEIN BESERTA APLIKASINYA DALAM KESEHATAN - Adi Santoso (Research Center for Biology-Indonesian Institute of Sciences, 2021)
Glycobiology is a study of the structure, biosynthesis, glycosylation and biology of glycans that are widespread in nature. Through the process of glycosylation which is one of the most post-translational forms of protein modification, macromolecular structures that are as diverse as glycoproteins can be formed. In other words, glycosylation is one of the most common structural modifications used by biological systems to expand proteomic diversity. This makes glycosylation a very high prevalence, estimated at 50-70% of all proteins are glycoproteins. Glycosylation can affect proteolysis patterns, ligand-receptor interactions, oncogenic signal transduction, body immunity, cell adhesion and cell matrix. Because of the high level of structural variability that arises from the glycosylation process, many new strategies can be made using the uniqueness of this glycoprotein modification, especially in the pharmaceutical field. This includes modifications in protein engineering in the expression systems of yeast, plant cells and mammalian cells.